Tryptophanyl-tRNA synthetase-1 (WARS-1) depletion and high tryptophan concentration lead to genomic instability in Caenorhabditis elegans - Mahmoud Izadi (12899508) (2024)
The fidelity of translation is ensured by a family of proteins named aminoacyl-tRNA synthetases (ARSs), making them crucial for development and survival. More recently, mutations in the tryptophanyl-tRNA synthetase 1 (WARS1) have been linked to various human diseases, from intellectual disability to various types of cancer. To understand the function of WARS1, we investigated the effect of WARS-1 depletion during the mitotic and meiotic cell cycle in the developing germline of Caenorhabditis elegans (C. elegans) and demonstrated the role of WARS-1 in genome integrity. wars-1 knockdown results in cell cycle arrest of the mitotically active germ cells. Such mitotic arrest is also associated with canonical DNA damage-induced checkpoint signaling in mitotic and meiotic germ cells. Significantly, such DNA checkpoint activation is associated with the morphological anomalies in chromatin structures that are the hallmarks of genome instability, such as the formation of chromatin bridges, micronuclei, and chromatin buds. We demonstrated that knocking down wars-1 results in an elevation of the intracellular concentration of tryptophan and its catabolites, a surprising finding emphasizing the impact of cellular amino acid availability and organismal/individual dietary uptake on genome integrity. Our result demonstrates that exposing C. elegans to a high tryptophan dosage leads to DNA damage checkpoint activation and a significant increase in the tryptophan metabolites. Targeting tryptophan catabolism, the least utilized amino acid in nature, can be important in developing new cancer therapeutic approaches. All in all, we have strong evidence that knocking down wars-1 results in defects in genomic integrity. Other Information Published in: Cell Death Discovery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41420-024-01917-4